Integrated Health Promotion Model in Intervention Animation Video Based For Improvement Knowledge : a Scoping Review - Andi haryati Hasrib; Huriati Huriati; Hasna Hasna; Rasdiyana Rasdiyana (Jurnal Ners, 2026)
Abstract Background : Animated video is increasingly used as a digital health education medium, yet no synthesis has mapped which health promotion models work best in which contexts. Objective : To map health promotion models integrated into animated video-based interventions for knowledge improvement, characterize their implementation, describe reported outcomes, identify evidence gaps (2021–2025), and build a model–context fit framework. Method : A scoping review following Arksey and O'Malley (2005), refined by Levac et al. (2010), reported per PRISMA- ScR , searching Scopus, PubMed Central, JMIR, and BioMed Central. Results : Thirty-eight articles were included, identifying seven models: SCT (n=17, 44.7%), HPM Pender (n=7, 18.4%), TPB (n=4, 10.5%), PRECEDE-PROCEED (n=4, 10.5%), HBM (n=3, 7.9%), IMB (n=2, 5.3%), and TTM (n=1, 2.6%). Thirty-four studies (89.5%) reported statistically significant knowledge improvement. SCT best suited broad awareness campaigns for resistant audiences; HPM Pender suitable chronic-disease self-management; PRECEDE-PROCEED suitable community-level, measurable change. Conclusion : Animated video interventions reliably improve knowledge across all seven models. This review contributes a model–context fit framework and a practical decision guide, while identifying four evidence gaps requiring longer follow-up, comparative trials, and standardized instruments. Keywords: health promotion model; animated videos; health education; health knowledge; nursing; scoping review